2011
DOI: 10.1143/jjap.51.010113
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Superconductor Terahertz Emitters: Fundamental Physics and Its Applications

Abstract: Coherent and continuous radiation sources of the electromagnetic (EM) waves at terahertz (1 THz = 10 12 c/s) frequencies using a mesa structure fabricated from high temperature superconducting Bi 2 Sr 2 CaCu 2 O 8þ single crystals are described with a special emphasis on the physics of the radiation mechanism and the applications. After the intensive studies of many mesas fabricated with different conditions, it is revealed that the ac-Josephson effect works as a primary driving mechanism of the radiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 77 publications
(146 reference statements)
3
49
1
Order By: Relevance
“…Based on their observations that the sub-THz emission can occur even with such a highly nonuniform T (r) variation containing a local hot spot with T (r) > T c in the higher I bias regime of the IVCs, these authors suggested that the hot spot formation may be beneficial to the synchronization of the N IJJs, an essential ingredient for obtaining intense sub-THz radiation. Numerical simulations of a hot spot [29], the fact that the c-axis resistance R c (T ) can be shunted by the hot spot due to T regions of negative differential resistivity, dρ c (T )/dT < 0 [5,29], the much narrower linewidth of 23 MHz in the high-I bias hot spot region than in the retrapping, low-I bias regime [30,31], and the lack of radiation from mesas with thicker Au electrodes [32] all tend to support their hypothesis that the hot spots play an essential role in the synchronization of the IJJs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their observations that the sub-THz emission can occur even with such a highly nonuniform T (r) variation containing a local hot spot with T (r) > T c in the higher I bias regime of the IVCs, these authors suggested that the hot spot formation may be beneficial to the synchronization of the N IJJs, an essential ingredient for obtaining intense sub-THz radiation. Numerical simulations of a hot spot [29], the fact that the c-axis resistance R c (T ) can be shunted by the hot spot due to T regions of negative differential resistivity, dρ c (T )/dT < 0 [5,29], the much narrower linewidth of 23 MHz in the high-I bias hot spot region than in the retrapping, low-I bias regime [30,31], and the lack of radiation from mesas with thicker Au electrodes [32] all tend to support their hypothesis that the hot spots play an essential role in the synchronization of the IJJs.…”
Section: Introductionmentioning
confidence: 99%
“…In rectangular mesas, the standing waves observed either by LTSLM or by rare-earth embedded polymer films formed along the mesa's length [6][7][8][9], although usually the observed f = f cav = c 0 /(2nw) [33], by excitation of the TM(1,0) thin rectangular EM cavity mode, where w is the mesa width both in the high-I bias reversible (R-type) region and in the low-I bias retrapping irreversible (IR-type) region, regardless of hot spot formation [19,20,[25][26][27][28]31,34]. Unfortunately, angular distribution experiments in the planes normal to the length and width of the rectangular mesa could not distinguish the difference between those associated standing wave models [35].…”
Section: Introductionmentioning
confidence: 99%
“…IJJ stacks, containing 500 -2000 junctions, have been patterned as mesas but also as bare IJJ stacks contacted by Au layers (GBG structures) 16,17,20,24 and as all-superconducting structures 11 . Emission frequencies range from 0.3 to 2.4 THz.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The radiation frequency can be tuned in a frequency range between 0.3 and 1.0 THz. 7,9 The characteristic properties of the superconducting THz emitter have been studied by many researchers. [10][11][12][13][14][15][16][17][18][19][20][21][22] In our previous study, 23 we proposed a transmission type of imaging system for application purpose using superconducting THz emitter, where the higher power THz emission is more desirable.…”
mentioning
confidence: 99%
“…Figure 2(a) shows current-voltage (I-V) characteristics of the IJJ-THz emitter used for the present experiment at the bath temperature of 45 K. The dimensions of the mesa device are 80 Â 400 Â 2.4 lm 3 fabricated by the Ar ion milling technique with a metallic mask. 9 The sub-THz wave radiation with a monochromatic frequency of 440 GHz was estimated by using interference pattern technique developed previously 23 at the bias point of I ¼ 60 mA and V ¼ 1.61 V as shown by the dotted line in Fig. 2.…”
mentioning
confidence: 99%